2022
DOI: 10.1051/ro/2021189
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing/remanufacturing based supply chain management under advertisements and carbon emissions process

Abstract: One of the most successful ways to get the word out about a product's popularity across all types of customers is through advertising. It has a valuable direct influence on increasing product demand. The supply chain model is developed for manufacturer and retailer, where advertisements are dependent on demand. The advertisement rate has been considered a function that has enhanced at a diminishing rate concerning time, although the growth rate slowed. During the manufacturing cycle, the market's demand is a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Studies had shown that increasing unit purchasing and remanufacturing costs of used products increased the quality and decreases the brand investment. Subhash et al [26] confirmed that the increasing cost of advertising provided a continuous increasing value of the total cost.…”
Section: Selling Price Dependent Demandmentioning
confidence: 95%
“…Studies had shown that increasing unit purchasing and remanufacturing costs of used products increased the quality and decreases the brand investment. Subhash et al [26] confirmed that the increasing cost of advertising provided a continuous increasing value of the total cost.…”
Section: Selling Price Dependent Demandmentioning
confidence: 95%
“…[24] developed a manufacturing strategy for a sustainable model that is energy efficient with flexible production. According to [13], a study investigated the feasibility of production and remanufacturing coordination for an integrated supply chain system. [8] provide an overview of a reverse logistics supply-chain strategy for customer satisfaction.…”
Section: The Decision-makers Have Been Provided With Managerial Insig...mentioning
confidence: 99%
“…Farrokh et al [37] dealt with an SCN model design that includes recycling and disposal processes and formulated a mixed-integer programming model that optimized SCN configuration, fluctuations, and operational risks. Fattahi et al [38] tackled a multi-period network modernization challenge, where consumer zones have stochastic price-dependent demand for multiple products.…”
Section: Effectiveness Of Multi-capacitated Logistics Under Scnmentioning
confidence: 99%
“…The model is semi-static because it involves inventory cost, ordering cost, the plant's capacity & warehouse, lead time, and buffer stock parameters in multi-periods and multi-products. Various other costs (shortage cost, cost of setting up the warehouse, and manufacturing cost of goods) and risk parameters have been proposed in various studies (Mohammed and Duffuaa, [11]; Choi et al, [23]; Kumar et al, [37]; Kugele et al, [42]; Sarkar et al, [56]) can be incorporated in the present model. Some exciting research areas for the future are:…”
Section: Limitations and Scope For Future Workmentioning
confidence: 99%